Building a sustainable infrastructure for covid-19 vaccinations long term. (21st June 2021) - Hodes, Simon; Majeed, Azeem
Abstract : With covid-19 booster vaccinations likely in the near future, now is the time to consider how to create a sustainable, long term infrastructure for vaccine delivery